Validation of set up for experimental analysis of reactive muffler for the determination of transmission loss: Part 1. (June 2018) - Kulkarni, Mahesh V; Ingle, Ravindra B
The internal combustion engine is the major source responsible for noise pollution. In an engine, the exhaust noise and the noise produced due to friction of various parts of the engine share maximum contribution to noise pollution. A muffler is a device used to reduce noise within the exhaust system. It is arranged along the exhaust pipe for the purpose of noise attenuation. In this article, the set up for experimental analysis is developed to predict the acoustic performance of reactive muffler using the two-load method, and it is validated by measuring transmission loss of known reactive muffler model by using finite element method. For the model, transmission loss obtained from experimental analysis was compared with that obtained from the finite element method. From the result, it can be concluded that the setup developed for experimental analysis is reliable to determine transmission loss of exhaust muffler, for low to mid frequency range.